1938
DOI: 10.1042/bj0322207
|View full text |Cite
|
Sign up to set email alerts
|

The water-soluble B-vitamins other than aneurin (vitamin B1), riboflavin and nicotinic acid required by the pig

Abstract: FROM the results of previous work [Birch et al. 1937; Chick et al. 1938, 1, 2] it was concluded that young pigs could be reared successfully on a diet of maize and purified casein with the addition of a suitable salt mixture, provided that nicotinic acid were also given. Similar experiments made on rats showed that the addition of nicotinic acid was not required for this species [Chick et al. 1938, 2].The fact that an extraneous source of nicotinic acid or its amide does not appear to be required by the rat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1940
1940
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Somewhat similar experiments have been reported on dogs (17)(18)(19)(20), on rats (21-25), on pigs (26)(27)(28)(29), and on pigeons (30,31). It is impossible to say at the present time which of these experimental blood dyscrasias may be the result of the deficiency that we are dealing with in our experiments on the monkey.…”
Section: Discussionmentioning
confidence: 52%
“…Somewhat similar experiments have been reported on dogs (17)(18)(19)(20), on rats (21-25), on pigs (26)(27)(28)(29), and on pigeons (30,31). It is impossible to say at the present time which of these experimental blood dyscrasias may be the result of the deficiency that we are dealing with in our experiments on the monkey.…”
Section: Discussionmentioning
confidence: 52%
“…Brain does not conserve vitamin B-6 as well as muscle during severe dietary vitamin B-6 deficiency. Early studies of vitamin B-6 deficiency reported seizures in dogs (Fouts et al 1938), pigs (Chick et al 1938) and rats (Chick et al 1940). In humans seizures have been observed as a result of dietary vitamin B-6 deficiency (Coursin 1955) and genetic disorders of vitamin B-6 metabolism (Footitt et al 2013;Dakshinamurti and Dakshinamurti 2014).…”
Section: Vitamin B-6 and Seizuresmentioning
confidence: 99%
“…Studies of animal nutrition have shown that many B group vitamins are concemed, directly or indirectly, in haemopoiesis (see Lemberg & Legge, 1949;Jukes, 1953). In particular, dietary deficiency of pyridoxine results in hypochromic anaemia in pigs, dogs and rats (Chick, Macrae, Martin & Martin, 1938;Fouts, Helmer & Lepkovsky, 1940;Kornberg, Tabor & Sebrell, 1945). The concentration of free protoporphyrin in the erythrocytes of pyridoxine-deficient pigs was found by Cartwright & Wintrobe (1948) to be markedly lower than that in the control animals, suggesting that this vitamin is directly concerned in the synthesis of protoporphyrin.…”
Section: J Lascellesmentioning
confidence: 98%